Bad Debts and the Cleaning of Banks' Balance Sheets: An Application to Transition Economies - Mitchell, Janet (Journal of Financial Intermediation, 2001)
This paper develops a framework for analyzing tradeoffs between policies for cleaning banks' balance sheets of bad debt when asymmetric information exists between banks and regulators regarding the amount of bad debt. The framework consists of a two-tier hierarchy composed of a regulator, banks, and firms. Hidden information and moral hazard are present at each tier of the hierarchy. The analysis identifies two types of effects of the regulator's policy choice: a direct effect on a bank's willingness to reveal its bad loans versus hiding them via loan rollovers, and an indirect effect on firm behavior as a function of the bank's response. The framework is applied to analyze tradeoffs between three policies: a laissez-faire policy, transfer of debt to an asset management company, and cancellation of debt inherited from a previous regime. Journal of Economic Literature Classification Numbers: G21; G28; G30; P34.